Polarization-controlled directional scattering for nanoscopic position sensing - Martin Neugebauer (Nature Portfolio, 2016)
High-refractive-index nanoantennas support magnetic and electric resonances that can be excited with structured light. Here, the authors exploit the interference of such resonances to achieve strong lateral directionality of the emission and utilize this effect for nanoscopic position sensing.